Effects of SiCp Content on the Microstructure and Mechanical Properties of SiCp/Mg-5Al-2Ca Composites. Issue 5 (May 2018) - Hai, Chang; Cuiju, Wang; Kunkun, Deng; Kaibo, Nie; Kun, Su; Ling, Liao; Hongxia, Wang; Libo, Tong
Abstract: The Mg-5Al-2Ca alloys reinforced by 2vol%, 5vol% and 10vol% 5 μm SiCp were fabricated by stir casting. The cast composites were subject to hot extrusion. In the cast composites, addition of SiCp disturbs the network distribution of Al2 Ca phase along grain boundaries. After extrusion, grains of the matrix are refined further and the Al2 Ca phase break into particulates. Moreover, the Al2 Ca phase and grain size can be further refined by the addition of SiCp. Compared with Mg-5Al-2Ca alloy, the addition of SiCp introduces obvious improvement of tensile yield strength (TYS) and work hardening rate, however, at the expense of elongation. Unlike the TYS, the ultimate tensile strength (UTS) of SiCp/Mg-5Al-2Ca composite does not change monotonously with increasing SiCp's content, and the highest UTS appears when the SiCp's volume fraction is 5%. The interfacial debonding between SiCp and Al2 Ca phase and cracked particles are considered as the main crack source for SiCp/Mg-5Al-2Ca composite.